Identifikasi Masalah yang Dialami Oleh Guru dan Siswa Pada Pelaksanaan Pembelajaran Geografi di Masa Pandemi Covid-19 - Fingki Maulana; Andrias; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2023)
The implementation of the online learning system during the Covid-19 pandemic caused many problems in its implementation. This study aims to find out the problems experienced by teachers and students in implementing online Geography lessons during the Covid-19 pandemic. This research method uses quantitative methods. Data was collected through observation, questionnaires and documentation described in descriptive statistics. The results showed that teachers experienced problems both from unstable internet networks, lack of internet quota availability, or lack of mastery of applications used in online learning, student indiscipline, lack of student motivation to take part in online learning and the teacher gave grades objectively according to students' abilities. Meanwhile, students experienced problems in mastering online learning support applications and the discipline of collecting assignments and obtaining grades with a percentage of 52%, 42.3%, and 52.5%, respectively